2009
DOI: 10.4049/jimmunol.0901748
|View full text |Cite
|
Sign up to set email alerts
|

IFN Regulatory Factor 5 Is Required for Disease Development in the FcγRIIB−/−Yaa and FcγRIIB−/− Mouse Models of Systemic Lupus Erythematosus

Abstract: This information is current as Lupus ErythematosusMouse Models of Systemic − / − RIIB γ Fc and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
105
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(117 citation statements)
references
References 88 publications
12
105
0
Order By: Relevance
“…Indeed, this is supported by the demonstration that autoreactive B cells are distinctly capable of internalizing, via BCR endocytosis, and responding to autoantigens in the absence of prior autoantibody production (42). Consistent with our data, more convincing data are provided by Richez et al, who found that type I IFN receptordeficient mice are not protected from SLE on an autoimmuneprone background (26).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Indeed, this is supported by the demonstration that autoreactive B cells are distinctly capable of internalizing, via BCR endocytosis, and responding to autoantigens in the absence of prior autoantibody production (42). Consistent with our data, more convincing data are provided by Richez et al, who found that type I IFN receptordeficient mice are not protected from SLE on an autoimmuneprone background (26).…”
Section: Discussionsupporting
confidence: 91%
“…1B). These data demonstrate that IRF5 is required for nephritisrelated IgG deposits in glomeruli induced to develop by pristane treatment and are consistent with those by Richez et al (26).…”
Section: Irf5supporting
confidence: 92%
See 1 more Smart Citation
“…For example, treating these mice with interferon accelerates disease in a T-cell like manner (Z. Liu, et al, 2010;Mathian, et al, 2005), while knocking out or inhibiting interferon-related genes slows or eliminates the development of lupus-like symptoms (Jorgensen, et al, 2007;Sharma, et al, 2005). These mice have been used to clarify the interactions between sex hormones and www.intechopen.com interferon in lupus etiology (Bynote, et al, 2008;Panchanathan, et al, 2009;Panchanathan, et al, 2010), and they serve as an excellent all-around model for spontaneous development of lupus.…”
Section: Mouse Models Allow the Study Of Ifn And Apoptosis Pathwaysmentioning
confidence: 99%
“…This gene is an interferon-regulating gene which will be described in section 5.2 below. It was discovered that knockout of IRF5 prevents or inhibits the development of lupus in MRL/lpr mice, Fc -/-Yaa mice, and pristine-injected mice (Richez, et al, 2010;Savitsky, et al, 2010;Tada, et al, 2011). Mouse models for lupus represent a powerful and flexible mechanism for investigating the role of multiple aspects of lupus.…”
Section: Mouse Models Allow the Study Of Ifn And Apoptosis Pathwaysmentioning
confidence: 99%